Regional Variation in Winter Foraging Strategies by Weddell Seals in Eastern Antarctica and the Ross Sea - Harcourt, Rob; Hindell, Mark A.; McMahon, Clive R.; Goetz, Kimberly T.; Charrassin, Jean-Benoit; Heerah, Karine; Holser, Rachel; Jonsen, Ian D.; Shero, Michelle R.; Hoenner, Xavier; Foster, Rose; Lenting, Baukje; et al. (Frontiers in Marine Science, 2021)
The relative importance of intrinsic and extrinsic determinants of animal foraging is often difficult to quantify. The most southerly breeding mammal, the Weddell seal, remains in the Antarctic pack-ice year-round. We compared Weddell seals tagged at three geographically and hydrographically distinct locations in East Antarctica (Prydz Bay, Terre Adélie and the Ross Sea) to quantify the role of individual variability and habitat structure in winter foraging behaviour. Most Weddell seals remained in relatively small areas close to the coast throughout the winter, but some dispersed widely. Individual utilisation distributions (UDi, a measure of the total area used by an individual seal) ranged from 125 km2 to 20,825 km2. This variability was not due to size or sex but may be due to other intrinsic states for example reproductive condition or personality. The type of foraging (benthic vs pelagic) varied from 56.6 ±14.9% benthic dives in Prydz Bay through 42.1 ± 9.4% Terre Adélie to only 25.1 ± 8.7% in the Ross Sea reflecting regional hydrographic structure. The probability of benthic diving was less likely the deeper the ocean. Ocean topography was also influential at the population level; seals from Terre Adélie, with its relatively narrow continental shelf, had a core (50%) UD of only 200km2, considerably smaller than the Ross Sea (1650 km2) and Prydz Bay (1700 km2). Sea ice concentration had little influence on the time the seals spent in shallow coastal waters, but in deeper offshore water they used areas of higher ice concentration. Marine Protected Areas (MPAs) in the Ross Sea encompass all the observed Weddell seal habitat, and future MPAs that include the Antarctic continental shelf are likely to effectively protect key Weddell seal habitat.